2013
DOI: 10.1111/bph.12211
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle relaxation and activation of the large conductance Ca++ – activated K+ (BKCa) channel by novel oestrogens

Abstract: BACKGROUND AND PURPOSEOestrogens can interact directly with membrane receptors and channels and can activate vascular BKCa channels. We hypothesized that novel oestrogen derivatives could relax smooth muscle by an extracllular effect on the α and β1 subunits of the BKCa channel, rather than at an intracellular site. EXPERIMENTAL APPROACHWe studied the effects of novel oestrogens on the tension of pre-contracted isolated rat aortic rings, and on the electrophysiological properties of HEK 293 cells expressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…Directly confirming the 17β-estradiol-BK channel functional interactions, we found that 17β-estradiol (100 nM) significantly increased the single BK channel NP o of inside-out excised membrane patches of UBSM cells ( Fig 3 ). These results are in support of earlier electrophysiological reports in non-UBSM cell types showing activation of the BK channels by 17β-estradiol [ 13 16 , 26 ]. Our single BK channel recordings were performed using symmetrical K + solutions with fixed Ca 2+ concentration and in the absence of signaling pathways that may alter BK channel P o .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Directly confirming the 17β-estradiol-BK channel functional interactions, we found that 17β-estradiol (100 nM) significantly increased the single BK channel NP o of inside-out excised membrane patches of UBSM cells ( Fig 3 ). These results are in support of earlier electrophysiological reports in non-UBSM cell types showing activation of the BK channels by 17β-estradiol [ 13 16 , 26 ]. Our single BK channel recordings were performed using symmetrical K + solutions with fixed Ca 2+ concentration and in the absence of signaling pathways that may alter BK channel P o .…”
Section: Discussionsupporting
confidence: 93%
“…However, emerging evidence in UBSM and other cell types suggests the existence of several non-genomic mechanisms of 17β-estradiol, which may acutely influence cell excitability and contractility. These non-genomic mechanisms include: inhibition of L-type Ca V channels [ 9 , 20 , 21 ], endothelial-dependent release of nitric oxide [ 22 ], activation of protein kinases [ 23 ], and activation of the BK channels [ 13 , 24 ]. Involvement of the BK channels in the mechanism of 17β-estradiol-induced response is supported by studies from non-UBSM cell types and recombinant systems expressing BK channels, which indicate the activation of BK channels by 17β-estradiol is dependent on their regulatory β1-subunit [ 5 , 13 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to their effects on channel gating, β subunits grant BK channels sensitivity to several physiologically important compounds, thus making these subunits targets for possible pharmacological interventions. For example, β1-containing BK channels but not channels formed by the α subunit alone appear to be the target of 17β-estradiol and other compounds such as estrogen analogues, anti-estrogens, and the bile salt component lithocholic acid (Valverde et al, 1999; Dick et al, 2001; Bukiya et al, 2009; Maher et al, 2013). The activation of BK channels by 17β-estradiol has been proposed as the possible mechanism that mediates the acute relaxation of vascular smooth muscle induced by the hormone (White et al, 1995; Ruehlmann et al, 1998).…”
mentioning
confidence: 99%